2020
DOI: 10.1242/dev.183418
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB signaling regulates the formation of proliferating Müller glia-derived progenitor cells in the avian retina

Abstract: Retinal regeneration is robust in some cold-blooded vertebrates, but this process is ineffective in warm-blooded vertebrates. Understanding the mechanisms that suppress the reprogramming of Müller glia into neurogenic progenitors is key to harnessing the regenerative potential of the retina. Inflammation and reactive microglia are known to influence the formation of Müller glia-derived progenitor cells (MGPCs), but the mechanisms underlying this interaction are unknown. We used the chick model in vivo to inves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 101 publications
1
63
0
Order By: Relevance
“…These findings indicate that shortly after acute retinal injury, MG activate a program involving NFkB signaling, TGFb signaling, and Id transcription factors that suppress neurogenic potential, and likely act to restore and maintain glial phenotype. This is consistent with our findings in the chick retina that activation of NFkB signaling suppresses the formation of MGPCs and promotes differentiation of progeny into glial cells 15 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These findings indicate that shortly after acute retinal injury, MG activate a program involving NFkB signaling, TGFb signaling, and Id transcription factors that suppress neurogenic potential, and likely act to restore and maintain glial phenotype. This is consistent with our findings in the chick retina that activation of NFkB signaling suppresses the formation of MGPCs and promotes differentiation of progeny into glial cells 15 .…”
Section: Discussionsupporting
confidence: 93%
“…In the zebrafish, inflammatory signals are necessary for MG reprogramming and ablation of microglia in the retina prior to injury impairs the process of neuronal regeneration 33,67 . In the chick retina, the ablation of microglia in the retina prevents the formation of proliferating MGPCs 68 , but this can be rescued by delivery of a pro-inflammatory cytokine (TNFSF15) or by pharmacological activation of NFkB-signaling 15 . However, in mammalian retinas, microglia interfere with MG-mediated neuronal regeneration; ablation of microglia promotes Ascl1-mediated neurogenesis and treatment with TNF decreases Ascl1-mediated MG reprogramming 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the recent developments were reported in either cold-blooded or warm-blooded vertebrates, some of of 12 which investigated molecular pathways that may improve the current understanding of the reprogramming of Müller glia in mammals. For example, a recent study by Palazzo et al (2019) investigated the role of the Nuclear Factor Kappa B (NF-kB) pathway in Müller glia reprogramming in chick embryos, which showed that a component of the NF-kB pathway expressed by Müller cells, inhibits the reprogramming of Müller glia into retinal neurons [79], providing targets that can potentially be responsible for the lack of regeneration of mammalian Müller cells into retinal neurones.…”
Section: Current Understanding Of the Regeneration Potential Of Müller Glia In Mammalsmentioning
confidence: 99%